Structural deformation behavior of Jacquardtronic lace based on the mass-spring model. Issue 10 (June 2017) - Li, Xinxin; Zhang, Aijun; Ma, Pibo; Cong, Honglian; Jiang, Gaoming
To simulate the structural deformation behavior of Jacquardtronic lace, which is formed on a multibar Jacquard Raschel machine and is widely used in female fashion, the key influencing factors on structural deformation were introduced and a tailored mass-spring model was built in which the lace was considered to be numbers of evenly distributed particles connected by elastane springs. These springs covered structural springs, restriction springs and spiral springs, respectively, created for ground pillars, Jacquard inlays, pattern lapping and elastane yarns. The elastane force on particles was analyzed to study motion state and deformation behavior with the explicit Euler method. The deformation simulated models were implemented by a simulator program via Visual C++ and were tested with a lace sample. Particular attention was paid to analyzing the effect of Jacquard structures and yarn tension on deformation and the detection model was introduced to avoid improper deformation caused by excessive yarn tension. The simulation results showed practicability and efficiency when compared with the real sample.